Beneficial effects of β-conglycinin on renal function and nephrin expression in early streptozotocin-induced diabetic nephropathy rats. Issue 1 (14th January 2014) - Yang, Hsin-Yi; Wu, Lin-Yi; Yeh, Wan-Ju; Chen, Jiun-Rong
<x content-type="archive" xml:space="preserve">Abstract</x> The objective of the present study was to investigate the effects of β-conglycinin and soya isoflavones on diabetic nephropathy (DN). DN was induced by an intravenous injection of streptozotocin (25 mg/kg) in spontaneously hypertensive rats. DN rats were divided into a non-diabetic group (C, control group) and three DN groups (D, DN with control diet; B, DN+control diet with one-eighth of casein replaced by β-conglycinin as the protein source; and I, DN+control diet with 0·01 % soya isoflavones). After a 4-week experimental period, we found that fasting blood sugar and plasma and kidney advanced glycation end product levels and 24 h urinary protein excretion of the B group were significantly lower than those of the D group and insulin sensitivity and nephrin expression of the B group were significantly higher than those of the D group. In addition, systolic blood pressure, angiotensin-converting enzyme activity, angiotensin II level and plasma TAG level of the B group were significantly lower than those of the D group, whereas only the levels of plasma TAG and thiobarbituric acid-reactive substances of the I group were lower than those of the D group. In conclusion, β-conglycinin may be beneficial for retarding DN progression and this effect cannot be completely explained by its isoflavone content.